Efektivitas Pembelajaran Model SrVER Berbantukan Media Augmented Reality dan Virtual Reality terhadap Hasil Belajar Siswa SMA - Baiq Sri Handayani; Tri Ayu Lestari; Anindita Suliya Hangesti Mandra Kusuma; Eni Suyantri; Gde Cahyadi Wirajagat; Izza Melati Sukma (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to analyze the effectiveness of the SrVER learning model assisted by Augmented Reality (AR) and Virtual Reality (VR) media in Biology Learning. The study employed a quasi-experimental method with a pretest–posttest nonequivalent control group design. The population comprised high school students in Mataram City, and samples were selected using purposive sampling. Data were collected through a validated multiple-choice test (25 items, α = 0.82). Data analysis used Quade’s Rank Analysis of Covariance followed by the Least Significant Difference (LSD) test. The findings revealed a significant difference (p < 0.001) in students’ learning outcomes between the conventional, AR-assisted SrVER, and VR-assisted SrVER classes. The AR-assisted SrVER group achieved the highest improvement (52.31%), showing that AR effectively enhances visual understanding in biological concepts. Therefore, integrating AR in visual-based learning is recommended to improve student engagement and learning outcomes in Biology Learning